2013
DOI: 10.1128/jcm.02735-12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fecal Lactoferrin in Toxin-Positive and Toxin-Negative Clostridium difficile Specimens

Abstract: Quantitative fecal lactoferrin was measured in 112 patients tested for toxigenic Clostridium difficile using glutamate dehydrogenase (GDH) and toxin immunoassays combined with tcdB PCR. Lactoferrin levels were higher in the GDH-positive/toxin-positive group (79 g/ml) than in the GDH-positive/toxin-negative/PCR-positive (21 g/ml) and the GDH-negative groups (13 g/ ml). Differences in fecal lactoferrin levels suggest variable presence or severity of C. difficile infection among toxin-positive and toxin-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…It has been previously demonstrated that fecal lactoferrin levels are higher in patients with detectable stool Clostridial toxin(s) [31], and that there is a high concordance between lactoferrin and calprotectin levels [10]. This suggests that there is an association between the degree of toxin production and clinical severity that also influences lactoferrin/calprotectin levels, but prior studies regarding this have reached contradictory conclusions [3236].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that fecal lactoferrin levels are higher in patients with detectable stool Clostridial toxin(s) [31], and that there is a high concordance between lactoferrin and calprotectin levels [10]. This suggests that there is an association between the degree of toxin production and clinical severity that also influences lactoferrin/calprotectin levels, but prior studies regarding this have reached contradictory conclusions [3236].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, others have reported on the utility of fecal lactoferrin testing for assessing severity of C. difficile infection (162), as a marker for infection associated with moxifloxacinresistant strains (163), and in testing algorithms as a first step in deciding which patients with diarrhea should be tested for C. difficile (159). It has also been used to determine the clinical significance of results using multistep algorithms that involve GDH screening and PCR confirmation (164). In the latter scenarios, lactoferrin levels were higher in patients who were GDH positive/ toxin positive than in GDH-positive/toxin-negative/PCR-positive or GDH-negative patients (164).…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…It has also been used to determine the clinical significance of results using multistep algorithms that involve GDH screening and PCR confirmation (164). In the latter scenarios, lactoferrin levels were higher in patients who were GDH positive/ toxin positive than in GDH-positive/toxin-negative/PCR-positive or GDH-negative patients (164). In a study by van Langenberg et al, the authors reported a negative predictive value of 92% when the manufacturer's cutoff was lowered from 7.25 g/ml to 1.25 g/ml (159).…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…Others have shown a significant association when comparing FC levels in toxin positive and GDH positive plus tcdA/tcdB PCR confirmed patients when compared to diarrhoea controls [24]. Similarly, FL has also been shown to be elevated in CDI patients [20], [25][27], with more recent studies suggesting a positive correlation with disease severity [28]–[30] and fluoroquinolone resistance [31]. There are however limitations with the published studies: these include their retrospective nature, limited phenotype data, lack of matched controls, use of non-quantitative tests, and variations in the assessment of CDI outcome measures.…”
Section: Introductionmentioning
confidence: 99%